2022
DOI: 10.1021/acs.est.1c05484
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Iodinated Aromatic Disinfection Byproducts: Acid Catalysis with H2OI+

Abstract: Iodinated aromatic disinfection byproducts (I-DBPs) are a group of nonregulated but highly toxic DBPs. The formation of I-DBPs is attributed mainly to HOI because it is the most abundant reactive iodine species in chloraminated water. In this study, we used computational modeling of thermodynamics to examine the mechanism of iodination of aromatic contaminants, e.g., dipeptides and phenols. Computational prediction of the energy barriers of the formation of iodinated tyrosylglycine (I-Tyr-Gly) (66.9 kcal mol −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…The proportions of polycyclic aromatics and phenolic iodinated DOM products exceeded 50%, indicating that aromatic structures were favorable for the binding of OM to iodine. ,, Moreover, the number of phenolic iodinated DOM products was significantly higher than that of polycyclic aromatic iodinated DOM products (Figure S8). Although the above organic compounds contain aromatic structures, phenolic compounds contain more ring-activating functionalities and are more conducive to electrophilic substitution of iodine compared to polycyclic aromatics with condensed aromatic structures. ,, Besides these two organic compounds, the remaining iodinated DOM products were highly unsaturated compounds (accounting for 49.7%). Highly unsaturated compounds are the most dominant component of DOM in groundwater, accounting for approximately 50% of all organic compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportions of polycyclic aromatics and phenolic iodinated DOM products exceeded 50%, indicating that aromatic structures were favorable for the binding of OM to iodine. ,, Moreover, the number of phenolic iodinated DOM products was significantly higher than that of polycyclic aromatic iodinated DOM products (Figure S8). Although the above organic compounds contain aromatic structures, phenolic compounds contain more ring-activating functionalities and are more conducive to electrophilic substitution of iodine compared to polycyclic aromatics with condensed aromatic structures. ,, Besides these two organic compounds, the remaining iodinated DOM products were highly unsaturated compounds (accounting for 49.7%). Highly unsaturated compounds are the most dominant component of DOM in groundwater, accounting for approximately 50% of all organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Although the above organic compounds contain aromatic structures, phenolic compounds contain more ring-activating functionalities and are more conducive to electrophilic substitution of iodine compared to polycyclic aromatics with condensed aromatic structures. 11,42,43 Besides these two organic compounds, the remaining iodinated DOM products were highly unsaturated compounds (accounting for 49.7%). Highly unsaturated compounds are the most dominant component of DOM in groundwater, accounting for approximately 50% of all organic compounds.…”
Section: Molecular Characteristics Of Organoiodine Compounds Inmentioning
confidence: 99%
“…In a study of formation mechanisms, Gao et al investigated formation of iodinated aromatic DBPs from H 2 OI + . Because it is the most abundant reactive iodine species in chloraminated water, HOI is typically assumed to be the active oxidant in high iodide waters.…”
Section: Drinking Water and Swimming Pool Disinfection Byproductsmentioning
confidence: 99%
“…In a study of formation mechanisms, Gao et al investigated formation of iodinated aromatic DBPs from H 2 OI + . 103 Because it is the most abundant reactive iodine species in chloraminated water, HOI is typically assumed to be the active oxidant in high iodide waters. However, as shown through computational modeling of thermodynamic results, new research found that H 2 OI + was key to the initiation of iodination in the formation of an iodinated peptide DBP (iodo-tyrosine-glycine).…”
mentioning
confidence: 99%
“…The primary goal of disinfection is to inactivate pathogenic microorganisms (e.g., viruses, protozoa, algae, etc.) and help to control the spread of waterborne diseases (e.g., cholera, typhoid). Nevertheless, the major downside of chemical disinfection (e.g., chlorination and chloramination) is that disinfectants (e.g., chlorine and chloramines) react with natural organic matter (NOM) to form disinfection byproducts (DBPs) of health concerns. ,, Trihalomethanes (THMs) and haloacetic acid (HAAs), two common classes of DBPs, are currently regulated by the United States Environmental Protection Agency (USEPA) at maximum contaminant limits (MCLs) of 80 and 60 μg/L, respectively. , The generation of emerging DBPs (e.g., iodinated THMs, N -nitrosodimethylamine [NDMA]) is also alarming because these emerging DBPs are often more toxic than the DBPs regulated by USEPA. Currently, NDMA is regulated in many regions. , For example, the California Department of Public Health established a notification levels of 10 ng/L, Canada set a national guideline value of 40 ng/L, and Australia adopted a target value of 100 ng/L for this contaminant in drinking water . Epidemiological studies revealed that DBPs in drinking water can be associated with several health issues including cancer, miscarriage, and birth defects. , As water cycles have multiple interconnected components (e.g., stormwater, sewage, and drinking water), DBPs can be introduced into a water cycle in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%